2012
DOI: 10.1259/dmfr/60907848
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in the assessment of benignity and malignancy of parotid masses

et al.

Abstract: Objectives: This study aimed to investigate the value of ultrasound in the identification of benign and malignant parotid masses. Methods: Data of 189 patients with parotid gland masses undergoing ultrasound-guided fineneedle aspiration (FNA), core biopsy or surgery were reviewed retrospectively and the presumed sonographic diagnoses were compared with the histopathology. The sensitivity, specificity and accuracy of sonographic diagnoses were assessed and the sonographic characteristics of those lesions, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 16 publications
1
32
2
5
Order By: Relevance
“…In our study it was found that most of benign tumours had ovoid shape (64.28%) on ultrasound while in malignant tumours most common shape observed was irregular (77.27%). This result was similar to the results of study carried out by S Wu et al 8 J. Evid. Based Med.…”
Section: Discussionsupporting
confidence: 93%
“…In our study it was found that most of benign tumours had ovoid shape (64.28%) on ultrasound while in malignant tumours most common shape observed was irregular (77.27%). This result was similar to the results of study carried out by S Wu et al 8 J. Evid. Based Med.…”
Section: Discussionsupporting
confidence: 93%
“…In our institutions, CT was reserved for those patients unable to undergo MRI. There are differing opinions on whether one modality is superior in differentiating between benign and malignant parotid masses, although literature supports MRI being accurate in characterising salivary gland masses and surrounding soft tissues well, and therefore, most of our patients underwent MRI prior to surgery.…”
Section: Introductionmentioning
confidence: 96%
“…Because of the diffuse growth pattern of ACC and posttherapeutic scar formation, the detection of tumor recurrence is challenging, especially as the low soft tissue contrast of contrast-enhanced CT or ultrasound examinations leads to a low diagnostic accuracy. 22,23 Hence, MRI is considered as superior in clinical routine due to its high soft-tissue contrast. 24,25 But as surgery and/or radiotherapy may cause significant alterations of tissue anatomy, exclusive morphological information offered by MRI may be insufficient to differentiate between posttherapeutical changes and tumor relapse.…”
Section: Discussionmentioning
confidence: 99%